Peranacangan Film Pendek Anak Bawah Kolong “Pembentukan Karakter Anak Melalui Seni Musik di Pariaman” - Muhammad Syahputra; syafwandi syafwandi (DEKAVE : Jurnal Desain Komunikasi Visual, 2021)
The design of this film is based on the fact that in the city of Pariaman there are still many  juvenile delinquencies that occur. Kota Pariaman does not yet have the means of information on what businesses have been done by some figures to overcome juvenile delinquency. The Darak Badarak art community, a music community located in the city of Pariaman, has members aged between 12-17 years. The Darak Badarak art community has recruited members from school dropouts and children who have an interest in playing music. The Darak Badarak art community is a little  gradually have succeeded in achieving achievements and improving the character of children who have been given learning during activities in the community, both in playing music training activities and other activities. This design aims to design audio-visual media in the form of short films, this film is designed to convey to society is an efficient way to tackle juvenile delinquency. This short film is designed based on the history of the establishment and the process that the Darak Badarak art community has gone through with dramatized reconstructions so that the public is interested and easily understands the information presented. Qualitative. This short film is designed using the Define, Design, Develop and Disseminate (4D) method, this method is used to facilitate the design in bringing out the creative and the production process. The expected design result is a short film with a historical background and the process that has been passed by the art community of DarakBadarak. , several items such as T-shirts, stickers, posters, trailers, Instagram accounts, cover flash cards and X banners to support the promotion of the Darak Badarak art community short film entitled "Anak Bawah Kolong".Keywords: film, docudrama, character, children and music